Verbal Instructions and Motor Learning: How Analogy and Explicit Instructions Influence the Development of Mental Representations and Tennis Serve Performance - Meier, Christopher; Frank, Cornelia; Gröben, Bernd; Schack, Thomas (Frontiers in Psychology, 2020)
To better understand the benefits of using analogies and explicit instructions, the underlying cognitive mechanism remains to be explored. The concept of chunking provides a promising approach to the cognitive mechanism of instructions, and can be approximated by analyzing athletes’ mental representations. The purpose of this study was to investigate the influence of analogy and explicit instruction on performance and the cognitive representations of the tennis serve in intermediate participants over the course of a five-week training period. Junior tennis players (N = 44; M = 11.5 years) were tested on their tennis serve and, based on their initial performance and their individual error patterns, assigned to one of three groups: an analogy group (N = 15), an explicit group (N = 15), or a control group (N = 14). Their performance and their mental representation structures were assessed prior to and after the five-week training period and again after a retention period of 14 days. Independent of group, findings demonstrated higher velocity from pretest to posttest. Participants of both the analogy and the explicit group showed enhanced accuracy over time and more functional mental representation structures. Thus, both analogy instruction and explicit instruction helped to structure mental representations in their long-term memory.